Mineral resources and budget of the country - E. A. Kozlovsky (Известия высших учебных заведений: Геология и разведка, 2017)
An issue about the role of mineral resources in the economic development of Russia has been considered. The divergence between the given possibilities and real budget has been marked. A conclusion has been made, that the system of the strategic investigation of mineral resources does not correspond the problem of country’s mineral safety provision and a complex of measures has been suggested, which are to lead to the improvement of the system of mineral deposits searching.